Impact of body composition and muscle health phenotypes on survival outcomes in colorectal cancer: a multicenter cohort - Ana Lúcia Miranda; Jarson Pedro da Costa Pereira; Iasmin Matias de Sousa; Glaucia Mardrini Cassiano Ferreira; Mara Rubia de Oliveira Bezerra; Gabriela Villaça Chaves; Fernanda F. Maciel; Leonardo Borges Murad; Sara Maria Moreira Lima Verde; Sílvia Fernandes Maurício; José Barreto Campello Carvalheira; Maria Carolina Mendes; et al. (Scientific Reports)
Abstract Body composition abnormalities are prognostic markers in several types of cancer, including colorectal cancer (CRC). Using our data distribution on body composition assessments and classifications could improve clinical evaluations and support population-specific opportune interventions. This study aimed to evaluate the distribution of body composition from computed tomography and assess the associations with overall survival among patients with CRC. In this multicenter cohort study, patients (N = 635) aged 18 years and older with CRC were observed for 12 to 36 months to assess outcomes. Skeletal muscle area (SM) and index (SMI), skeletal muscle radiodensity (SMD), intermuscular adipose tissue (IMAT), subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) were evaluated, and classified based on tertile distributions. Low muscle mass (SMI) and poor muscle composition (SMD) were independent predictors of mortality regardless of follow-up period. This risk of mortality increased to more than 3-fold when combining both low SMI and low SMD (HRadjusted 3.1, 95% CI 1.8 to 5.4, respectively). Our study indicates that body composition characteristics may vary across countries, highlighting the need for developing sex- and population-specific cutoff values for computed tomography assessments in patients with different types of cancer.